2020
DOI: 10.3389/fpsyg.2020.564430
|View full text |Cite|
|
Sign up to set email alerts
|

Cooperative and Individual Mandala Drawing Have Different Effects on Mindfulness, Spirituality, and Subjective Well-Being

Abstract: Mandala drawing was first practiced by Tibetan buddhists and then developed by Carl Gustav Jung, who felt certain that mandala drawing has the function of integrating psychological division, enhancing psychological harmony, and preserving personality integrity. Previous studies on mandala drawing have mainly focused on alleviating people’s negative emotions, such as anxiety and depression. Therefore, this study explored the effect and mechanism of mandala drawing on the improvement of subjective well-being (SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
(65 reference statements)
0
25
0
1
Order By: Relevance
“…Emotional components are divided into positive and negative emotions, which are relatively independent and subordinate to SWB (Jebb et al, 2020). Previous studies have found that SWB is positively correlated with mindfulness and spirituality (Liu et al, 2020a), and LKM can improve the mindfulness, spirituality, and SWB of flight attendants (Liu et al, 2020b).…”
Section: Loving-kindness Meditation Mindfulness Spirituality and Subj...mentioning
confidence: 99%
“…Emotional components are divided into positive and negative emotions, which are relatively independent and subordinate to SWB (Jebb et al, 2020). Previous studies have found that SWB is positively correlated with mindfulness and spirituality (Liu et al, 2020a), and LKM can improve the mindfulness, spirituality, and SWB of flight attendants (Liu et al, 2020b).…”
Section: Loving-kindness Meditation Mindfulness Spirituality and Subj...mentioning
confidence: 99%
“…(ii) Mandala drawing tasks (Couch, 1997;Liu et al, 2020;Smitheman-Brown & Church, 1996): Also known as mandala painting, mandala drawing can be described as a process of drawing or painting a circle that gradually turns into a complete mandala flower like what one sees a pattern when peeking into a kaleidoscope. However, this form of mandala art therapy has already gone far beyond that.…”
Section: Mandala Art Therapymentioning
confidence: 99%
“…Several studies (e.g., Liu, 2021;Liu et al, 2020;Henderson, Rosen, & Mascaro, 2007) have found the benefits of mandala art therapy though these benefits do not relate exactly to mandalas per se, but rather, more importantly, the process of applying the mandala as art therapy for stress, anxiety and depression (see Liu, 2012, for detail).…”
Section: Mandala Art Therapymentioning
confidence: 99%
“…Recent studies have shown the impact of mindfulness-based intervention guidance on occupational mental health of medical staff. Health care providers are using mindfulness practices to address mental and physical stress, emotional distress and burnout, while improving empathy, job satisfaction and well-being [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%